Making poor Haitians count : poverty in rural and urban Haiti : based on the First Household Survey for Haiti - Verner, Dorte (World Bank WashingtonUS, 2008)
Analyzes poverty in Haiti based on the First Living Conditions Survey of 97,186 households covering the whole country and representative at the regional level.